Interactive patterns of interactions for a mind mapping multimedia courseware - Saleem N.H.; Sidhu M.S.; Adnan N.; Shafeek N.A.; Yousif M.M.A. (2023)
Mind mapping is an illustration approach that has been used to facilitate the process of learning and the visualization of concepts better. In these days the utilization of mind mapping approaches in education have been increased significantly due to its success and its positive effect on students understanding especially in the Geography subjects which concepts are often difficult to visualize and to observe. In this paper we propose the use of multimedia and CAL applied in mind mapping in the geography of Malaysia by designing interactive patterns. An evaluation was conducted in some elementary schools to show the result of using this courseware in the education section. The project consists of a number of interactive pages designed to help Malaysian students aged between (11-13) years old, to visualize their understanding on the principles of geography in general, and the geography of Malaysia specifically, using their native language (Malay language). 2011 IEEE.